Project approach to the development of rural tourism - M. V. Andreeva; I. V. Kryukova; E. N. Yakovleva (Вестник университета)
The authors of the article provide an overview of scientific approaches to the definition of the essence and role of event and gastronomic tourism against the backdrop of the rural tourism promotion currently carried out. The interrelation between all the aforementioned types of tourism and the expediency of their joint development are substantiated. The necessity of holding events in order to smooth out the seasonality of rural tourism and attract tourists interested not only in standard services of rural guest houses but also in entertainment events is proved. Special emphasis is placed on the application of the project approach to the process of creating events. A description of the festivals held in the Vologda region is provided. The main problems of the implementation of project management at the municipal level are identified. The possibility of holding gastronomic festivals within the clusters operating in the region is considered. The example of the «SyrFest» gastronomic festival is used to demonstrate a possible project structure designed for such event.